Overview of mechanisms of antibiotic resistance in Pseudomonas aeruginosa: an ocular perspective - Subedi, Dinesh; Vijay, Ajay Kumar; Willcox, Mark (Clinical and experimental optometry, 2018)
Treatment of Pseudomonas aeruginosa eye infections often becomes a challenge due to the ability of this bacterium to be resistant to antibiotics via intrinsic and acquired mechanisms. Transfer of resistance due to interchangeable genetic elements is an important mechanism for the rapid transfer of antibiotic resistance in this pathogen. As a result, drug-resistant strains are becoming increasingly prevalent worldwide. This review systematically analyses data from recent publications to describe the global prevalence and antibiotic sensitivity of ocular P. aeruginosa. Thirty-seven studies were selected for review from PubMed-based searches using the criteria 'microbial keratitis OR eye infection AND Pseudomonas aeruginosa AND antibiotic resistance' and limiting to papers from 2011 onward, to demonstrate the antibiotic resistance from isolates from around the world. Subsequently, we reviewed the ways in which P. aeruginosa can become resistant to antibiotics. Both the rate of isolation of bacteria in general (79 per cent of cases), and prevalence of P. aeruginosa (68 per cent of all isolates) were highest in contact lens-related microbial keratitis. The average resistance rate to common ocular antibiotics such as ciprofloxacin (9 per cent), gentamicin (22 per cent) and ceftazidime (13 per cent) remained relatively low. However, there were large variations in resistance rates reported in studies from different countries, for example resistance to ciprofloxacin reached up to 33 per cent. We next reviewed the types of mobile genetic elements (MGEs) such as plasmids, integrons and transposons that are frequently associated with drug resistance in P. aeruginosa. MGEs are important for the transmission of resistance to beta-lactams and aminoglycosides and recently have been shown to be potential factors for the transmission of fluoroquinolone resistance. Studies on the molecular mechanisms of resistance transfer in ocular P. aeruginosa have begun to be reported and will provide valuable information on the emergence of new antibiotic resistance and potential to treat resistant strains.